Effects of 0.5% tetracaine hydrochloride on central corneal thickness and intraocular pressure - Manassakorn,A. (IOS Press, 2015)
Background: Intraocular pressure (IOP) is the most important risk factor in glaucoma. Before each measurement, anesthetic eye drop must be applied. The effect of these eye drops may affect the central corneal thickness (CCT) and the IOP. Objective: We investigated the effect of 0.5% tetracaine hydrochloride on central CCT and IOP in glaucoma patients. Methods: Glaucoma subjects aged ≥18 years, with spherical refractive error <±6 diopters(D) and astigmatism ≤3D were included. All underwent CCT and IOP measurement using Orbscan II and air-puff tonometer at baseline, and 1, 3, 5, 7, 9, 11, 13, and 15 minutes after application of 0.5% tetracaine hydrochloride. Results: There were 19 and 24 eyes eligible for CCT and IOP measurements. The mean±SD ages were 62.7±8.2 and 62.9±8.3 years. The mean±SD CCT at baseline was 527.8±32.2 μm. The mean±SD IOP at baseline was 13.2±5.6 mmHg. Although CCT did not change from baseline (p = 0.071), IOP significantly decreased from baseline at three, seven, and 11 minutes (p = 0.003, <0.001, and 0.002). Conclusions: CCT and IOP change trends were different. Although IOP decreased from baseline, CCT was unchanged.